Glycosaminoglycan depletion increases energy dissipation in articular cartilage under high-frequency loading. (October 2020) - Han, Guebum; Boz, Utku; Eriten, Melih; Henak, Corinne R.
Abstract: High-frequency material behavior of cartilage at macroscopic lengths is not widely understood, despite a wide range of frequencies and contact lengths experienced in vivo . For example, cartilage at different stages of matrix integrity can experience high-frequency loading during traumatic impact, making high-frequency behavior relevant in the context of structural failure. Therefore, this study examined macroscopic dissipative and mechanical responses of intact and glycosaminoglycan (GAG)-depleted cartilage under previously unexplored high-frequency loading. These dynamic responses were complemented with the evaluation of quasi-static responses. A custom dynamic mechanical analyzer was used to obtain dynamic behavior, and stress relaxation testing was performed to obtain quasi-static behavior. Under high-frequency loading, cartilage energy dissipation increased with GAG depletion and decreased with strain; dynamic modulus exhibited opposite trends. Similarly, under quasi-static loading, equilibrium modulus and relaxation time of cartilage decreased with GAG depletion. The increased energy dissipation after GAG depletion under high-frequency loading was likely due to increased viscoelastic dissipation. These findings broaden our understanding of fundamental properties of cartilage as a function of solid matrix integrity in an unprecedented loading regime. They also provide a foundation for analyzing energy dissipation associated with cartilage failure induced by traumatic impact. Graphical abstract: Image 1 Highlights: Macroscopic cartilage dissipation is investigated under high-frequency loading. Glycosaminoglycan deletion increases macroscopic cartilage dissipation. Macroscopic cartilage dissipation is strain-dependent. Glycosaminoglycan deletion decreases moduli and relaxation time of cartilage. Findings extend understanding of macroscopic dissipation under traumatic loading.